How Creative Engagement and Innovation Drive Growth in Manufacturing SMEs in South Africa - Maziriri, Eugine; Chuchu, Tinashe; Nyagadza, Brighton (International Research Journal of Business Studies, 2025)
This study investigates how green transformational leadership fosters creative process engagement to drive green product and process innovations, ultimately enhancing firm innovative performance and SME business growth within South Africa’s manufacturing sector. A quantitative survey was administered to 304 manufacturing SME managers in the Gauteng province, South Africa. Employing Partial Least Squares Structural Equation Modelling (PLS-SEM), the study tested hypothesised relationships among green transformational leadership, creative process engagement, green innovation (both product and process), firm innovative performance, and SME business growth, while also examining the moderating effect of top management support. Empirical results reveal that green transformational leadership significantly promotes engagement in the creative process, which drives green product and process innovations. These innovations contribute to improved firm innovative performance, positively influencing SME business growth. Moreover, top management support strengthens the relationship between innovative performance and business growth, underscoring its critical role in facilitating sustainable competitive advantage. By integrating Schumpeter’s innovation theory with the natural resource-based view, this research offers novel insights into the interplay between green leadership, creativity, and sustainable business outcomes in an emerging economy context. It fills a notable gap in the literature by focusing on South African small and medium-sized manufacturing enterprises (SMEs). It provides actionable recommendations for leaders and policymakers seeking to integrate sustainability into their strategic growth initiatives.